FIRST RECORD OF CARNIVORA (PUMA LINEAGE, FELIDAE) IN THE UQUÍA FORMATION (LATE PLIOCENE–EARLY PLEISTOCENE, NW ARGENTINA) AND ITS SIGNIFICANCE IN THE GREAT AMERICAN BIOTIC INTERCHANGE (Ameghiniana, 2019)
The fossil record of the puma lineage in the Americas is scarce, and many doubts have been raised as to the origin, radiation, and migration events of the group. In this study, we present and analyze qualitative- and quantitatively a complete left calcaneum, collected by Enrique de Carles at the beginning of twentieth century. The element is relatively small-sized, slender-shaped, with a long and latero-medially compressed tubercle, calcaneal canal obliterated by a ridge that connects the ectal and sustentacular facets, sustentacular facet proximo-medially projected, quadratus plantae process reduced, groove for the flexor digitorum lateralis markedly delimited, and cuboidal facet located on the transverse plane. The comparative analysis allowed us to confidently assign the fossil remain to the puma lineage. Given the preservation of a single autopodial element and the unique combination of features of the remain (not present in any specimens or species analyzed), we propose assigning the remain to gen. et sp. indet. The morphology of the element suggests cursorial adaptations, in an intermediate degree between living South American species and cheetahs. Despite the lack of exact stratigraphic provenance, the fossil studied represents the first carnivoran known for the Uquía Fm., and at least one of the earliest records of the puma lineage in America, and of Felidae in South America. These results highlight the already established high value of the Quebrada de Humahuaca for understanding the Great American Biotic Interchange and the need for future prospective campaigns in the region. http://dx.doi.org/10.5710/AMGH.31.03.2019.3206